واقع اهتمام إدارة الموارد البشرية بأبعاد الثقافة التنظيمية )القيم المعتقدات التوقعات ( لتشجيع الاستثمار في مواردها البشرية - اسلافي مصطفى; دمانه عمر (My University, 2024)
تهدف الد ا رسة الى معرفة واقع اهتمام إدارة المنشآت الرياضية بأبعاد الثقافة التنظيمية من اجل تعزيز وتشجيع الاستثمار في مواردها البشرية. ولتحقيق هذا الهدف تم تطبيق المنهج الوصفي باستخدام استبيان تم اعداده خصيصا لهذه الد ا رسة، والتي تم تطبيقه على 28 عينة من الموظفين المتواجدين على مستوى المسبح النصف الأولمبي بتيميمون والمركب الرياضي عبد الحميد كرمالي بتيميمون والقاعة المتعددة الرياضات بتيميمون . حيث اسفرت نتائج الد ا رسة على ان القيم التنظيمية والمعتقدات التنظيمية ليس لها دور في تشجيع الاستثمار داخل المنشآت الرياضية في موردها البشري. بينما التوقعات التنظيمية لها دور في تشجيع الاستثمار داخل المنشآت الرياضية في موردها البشري.
دراسة ميدانية: بعض المنشآت الرياضية ولاية تيميمون
To summarize: The study aims to know the reality of sports facilities management’s interest in the dimensions of organizational culture in order to enhance and encourage investment in its human resources. To achieve this goal, the descriptive approach was applied using a questionnaire prepared specifically for this study, which was applied to 28 samples of employees present at the level of the semi-Olympic swimming pool in Timimoun, the Abdelhamid Karmali Sports Complex in Timimoun, and the Multi-Sports Hall in Timimoun. The results of the study revealed that organizational values and organizational beliefs have no role in encouraging investment within sports facilities in their human resources. While organizational expectations have a role in encouraging investment within sports facilities in their human resources.